Building digital libraries : a how-to-do-it manual - Reese, Terry Jr.; Banerjee, Kyle. (New York : Neal-Schuman Publishers, 2008)
It is a tool kit for the new world of digital libraries. It demystifies the challenges of designing, constructing, and maintaining a digital repository.It also covers both the fundamentals of digital library theory and the details of how to implement a digital collection.
Includes bibliographical references and index.
uaj 02/05/13
Loans
Keywords: Digital libraries